2009
DOI: 10.1182/blood-2008-06-162040
|View full text |Cite
|
Sign up to set email alerts
|

VEGF-mediated cross-talk within the neonatal murine thymus

Abstract: Although the mechanisms of cross-talk that regulate the hematopoietic and epithelial compartments of the thymus are well established, the interactions of these compartments with the thymic endothelium have been largely ignored. Current understanding of the thymic vasculature is based on studies of adult thymus. We show that the neonatal period represents a unique phase of thymic growth and differentiation, marked by endothelium that is organized as primitive, dense networks of capillaries dependent on vascular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
1
10

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(69 citation statements)
references
References 42 publications
4
54
1
10
Order By: Relevance
“…The best fit with the experimental data was obtained when different sets of parameters were used in the modeling of the pre-natal and post-natal thymocyte dynamics, suggesting that the processes corresponding to these stages are characterized by different rates. This discontinuity during birth in thymocyte dynamics is supported by experimental data, which showed that in the case of proliferation, the fetal thymus has greater proliferation in thymocytes than the post-natal thymus12, and the neo-natal thymus has a greater proliferation of thymocytes than the adult thymus11. This particular pattern of proliferation is what the models also revealed and suggests that discontinuity in proliferation rates during birth happens normally in the thymus and birth actually resets the development pattern of the thymus for the remainder of the post-natal life.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The best fit with the experimental data was obtained when different sets of parameters were used in the modeling of the pre-natal and post-natal thymocyte dynamics, suggesting that the processes corresponding to these stages are characterized by different rates. This discontinuity during birth in thymocyte dynamics is supported by experimental data, which showed that in the case of proliferation, the fetal thymus has greater proliferation in thymocytes than the post-natal thymus12, and the neo-natal thymus has a greater proliferation of thymocytes than the adult thymus11. This particular pattern of proliferation is what the models also revealed and suggests that discontinuity in proliferation rates during birth happens normally in the thymus and birth actually resets the development pattern of the thymus for the remainder of the post-natal life.…”
Section: Discussionmentioning
confidence: 73%
“…Relative to the adult thymus, the neonatal thymus has greater thymocyte proliferation and a predominance of immature thymocytes11. The proliferation of the DN and DP thymocyte populations is higher in the fetal thymus than in the post-natal one12.…”
mentioning
confidence: 96%
“…This suggests that VEGF plays an important role in ATI (Cimpean et al 2008). A rapid reduction in the dense capillaries within the thymus and a significant decrease in the number of thymocytes were observed when VEGF signaling was inhibited in the neonatal life period compared to the adult stages (Cuddihy et al 2009). More recently, in LPS-induced ATI as a primary event, both VEGF expression in neonatal thymic tissue and number of TECs were shown to decrease simultaneously in a time-dependent fashion (Zhou et al 2016).…”
Section: Vascular Endothelial Growth Factor Signalingmentioning
confidence: 99%
“…VEGF has been involved in the cross-talk between the hematopoietic and epithelial compartments of the neonatal thymus (Cuddihy et al, 2009), but its role in the regulating the growth and proliferation of adult thymocytes remains unclear. Although VEGF and VEGFR were found to be hyperexpressed by immunohistochemistry in thymoma and thymic carcinomas (Cimpean et al, 2008), VEGF levels were previously found to be similar in the sera of patients with thymic tumors and healthy controls (Sasaki et al, 2001).…”
Section: Discussionmentioning
confidence: 99%